Aquatic Exercise at Thermoneutral Water Temperature Enhances Antitumor Immune Responses - Lee, Boae; Kim, Geona; Jo, Yuna; Lee, Byunghyuk; Shin, Yong-Il; Hong, Changwan (Immune network, 2019)
Despite the broad rehabilitative potential of aquatic exercises, the relationship between aquatic exercise and the immune system has not been fully elucidated to date. In particular, there are few specific and delicate immunological approaches to the effect of water temperature on immunity. Thus, we examined the effect of water temperature on immunity during aquatic exercise. The animal tumor model was adopted to examine the impact of aquatic exercise at thermoneutral temperature (TT; 29°C) on immunity compared with aquatic exercise at body temperature (BT; 36°C). Tumor-bearing mice were made to swim in TT water or in BT water for 3 wk and immune cells and their functional activity were analyzed using FACS. Tumor growth was significantly suppressed in mice that exercised in TT than in BT water. The tumor control correlated with the increased number of NK (2-fold), γδT cells (2.5-fold), NKT (2.5-fold), and cytotoxic CD8 T cells (1.6-fold), which play a critical role in anti-tumor immune responses. Furthermore, the functional activity was dramatically improved in the TT group, showing enhanced production of IFNγ in CD8 T cells compared with the BT group. This study demonstrates that aquatic exercise in TT water may improve protective immune responses more effectively than in BT water. Although the effects of water temperature on immune function need further verification in humans, this study suggests that water temperature in human hydrotherapy may be important for improving immune function.